OBSERVATIONS ON SOME ASPECTS OF SPOILAGE IN FRESH AND FROZEN PRAWNS - Pillai, V Krishna; Shsstri, P V K; Nayar, M R (Indian Journal of Fisheries, 2011)
THE prawn freezing factories in Cochin receive their supplies of raw materialsfrom all over the West Coast. Some factories have separate peehng centresin most of these places and the prawns collected from nearby fishing villagesare peeled and deveined or beheaded and deveined as the case may be, cleanedand packed in ice at these centres before transporting to the factories. Itoften happens that the material thus transported takes more than 24 hoxirsto reach the factories. Icing of the material at the peeUng site helps in preventingbacterial spoilage during the long period of transport. But thesuccess of icing will largely depend on the amount of ice used and how it isapplied. If the requisite quantity of ice is not used the material will not onlybe not cooled to the desired level but its temperature will rise up during thelong trip to the factory creating favourable conditions for normal spoilageprocesses to continue.